The Effect of Problem-Based Learning with A Culturally Responsive Teaching Approach on Understanding the Concept of Acids and Bases - Putri, Felia Annisa; Sumarti, Sri Susilogati; Harjono (Universitas Negeri Semarang, 2025)
Chemistry learning on acid-base material needs to be associated with the local cultural context to make it more meaningful for students. This study aims to determine the effect of problem-based learning with the CRT approach on the understanding of acid-base concepts. One of the implementations is done through the activity of identifying pH in batik coloring waste as part of the local culture around SMA Negeri 1 Juwana. The research used a quasi-experimental design with a Nonequivalent Control Group Design model. The research subjects were grade XI students, with grade XI-4 as the experimental class that received treatment in the form of problem-based learning with the CRT approach, and grade XI-5 as the control class with problem-based learning without the CRT approach. The results showed that problem-based learning with the CRT approach had a significant effect on the understanding of the acid-base concept. This is demonstrated by the results of statistical tests that show a significant difference in concept understanding between the experimental and control classes. The influence of problem-based learning with the CRT approach, based on the effect size test value, is 0.778 (medium category). Based on this, the CRT approach in the PBL model is proven to have an effective impact on students' understanding of the acid-base concept.